Perbedaan Self-Esteem Peserta Didik Kelas XI IPS Berdasarkan Usia dan Nilai Akademik di Madrasah Aliyah Negeri 1 Jember - Erna Paramitha (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
This study aims to analyze differences in the self-esteem levels of Class XI Social Studies students at MAN 1 Jember based on age and academic achievement. Self esteem, as a psychological aspect encompassing academic, social, and physical dimensions, influences learning motivation, social interactions, and academic performance. The research questions examine whether there are significant differences in self-esteem based on age and academic achievement. A quantitative approach with a survey design was employed, involving the entire population of 137 students. The research instrument used was the validated and reliable Lawrence Self-esteem Questionnaire (LAWSEQ). Data were analyzed using Multivariate Analysis of Variance (MANOVA). The results indicate that age significantly affects social self-esteem (p = 0.000; η² = 0.127) but not academic or physical self-esteem. Meanwhile, academic achievement has a stronger influence, particularly on social self-esteem (p = 0.000; η² = 0.301). Students with higher academic achievement tend to exhibit better self-esteem, though the relationship is not always linear. The study concludes that age and academic achievement are crucial factors to consider in developing guidance programs to enhance students' self-esteem, especially in the social dimension. These findings can serve as a reference for educators and parents in creating a supportive learning environment for students' psychological development.
Reuploud Repository hasyim Juni 2026 :: Finalisasi Repositori File 4 Juni 2026_Kurnadi
Keywords: self-esteem; age; academic achievement; students; MANOVA